2013
DOI: 10.4276/030802213x13651610908416
|View full text |Cite
|
Sign up to set email alerts
|

Drawing on Wilcock: An Investigation of the Impact of Her Published Work on Occupational Therapy Practice and Research

Abstract: occupational therapy, practice and research.Introduction: Ann Wilcock's published work identifies the fundamental importance of occupation in promoting health, wellbeing and even survival. Despite the implications for occupational therapy, the impact of her work has not been comprehensively explored. This research investigated how her ideas were used in published research from 1993 to 2007.Method and findings: Mixed methods obtained two sets of data. First, qualitative data from a textual analysis of Wilcock's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Hammell (2014) suggested that Wilcock’s (2007) framework for transforming health and wellbeing through Doing, Being, Belonging and Becoming is essentially theoretical, with Kosma et al. (2013) encouraging a need to generate evidence for these concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Hammell (2014) suggested that Wilcock’s (2007) framework for transforming health and wellbeing through Doing, Being, Belonging and Becoming is essentially theoretical, with Kosma et al. (2013) encouraging a need to generate evidence for these concepts.…”
Section: Discussionmentioning
confidence: 99%
“…She also noted many therapists were unfamiliar with the OPH, contributing to a theory practice gap (Kielhofner, 2005) and reluctance to adopt the dimensions into practice. Other authors, who have proposed measures to make the paradigm more accessible (Kosma et al, 2013), have also recognized the lack of awareness of the OPH within the profession. Stagnitti (2010) used the dimensions to explore play as an essential occupation.…”
Section: Hitch Et Almentioning
confidence: 98%
“…These lectures by Wilcock are followed by a selection of relevant articles published in BJOT. Kosma et al (2013) explored the impact of Wilcock's work on research published between 1993 and 2007. They sought to establish the core concepts of Wilcock's published work, how they have been interpreted in occupational therapy research and the implications for the profession.…”
Section: About the Bjot Ann Wilcock Collectionmentioning
confidence: 99%
“…Two authors who have developed work from Wilcock and published in BJOT are Wendy Bryant and Gail Whiteford. Bryant, one of the authors of Kosma et al (2013), made the concept of occupational alienation the focus of her Casson Memorial Lecture (Bryant, 2016). Whiteford's seminal article on occupational deprivation (Whiteford, 2000) expanded on Wilcock's original definition and proposed it as a global challenge for the 21st century.…”
Section: About the Bjot Ann Wilcock Collectionmentioning
confidence: 99%